Studi Komparatif: Model Pembelajaran Kooperatif Tipe Jigsaw dan Number Head Together dalam Pembelajaran IPA pada Siswa Sekolah Menegah Pertama - Nur Indah Sari; Fandi Ahmad (Jurnal Studi Guru dan Pembelajaran, 2024)
The focus of this quasi-experimental study is to compare the scientific learning outcomes of eighth-grade students at SMP Frater Makassar who are taught using the Jigsaw learning model with the outcomes of students taught using the Number Head Together (NHT) learning model.The purpose of this quasi-experimental study is to compare the scientific learning outcomes of eighth-grade Makassar Frater Junior High School students who are taught using the Jigsaw and Number Head Together (NHT) learning models. Posttest-only control design is used in research. All of the junior high school students in Class VIII at Frater were the study's population. The research sample consisted of 30 and 29 students from Class VIII B (who were taught using the NHT model) and Class VIII C (who were taught using the Jigsaw model), as selected by the purposive sampling technique. Data collection techniques through the administration of learning outcomes tests. Data analysis techniques using SPSS 12.0. The Jigsaw learning model was used to teach students, and the average learning outcomes were different. The students' learning outcomes were classified as high, with a standard deviation of 11.603 and an average of 79.17. Students that were taught using the NHT learning paradigm had learning outcomes of 69.48 with a standard deviation of 12.841, which was considered high. The T test results show that tcount = 3.65 and ttable = 2.003 so that the tcount > ttable is obtained with a significance level of 0.004, where H1 = Sig < 0.05 (5%) so that H1 is accepted. Based on the analysis and findings, it can be said that the Jigsaw Type cooperative learning model outperforms the NHT Model in terms of enhancing the science learning outcomes for Makassar Frater Junior High School Class VIII students.